Exploring the Role of Executive Functioning Measures for Social Competence Research. (September 2016) - Stichter, Janine P.; Christ, Shawn E.; Herzog, Melissa J.; O'Donnell, Rose M.; O'Connor, Karen V.
Numerous research groups have consistently called for increased rigor within the evaluation of social programming to better understand pivotal factors to treatment outcomes. The underwhelming data on the essential features of social competence programs for students with behavior challenges may, in part, be attributed to the manner by which available measures are accessed within applied research. The growing literature highlighting the bidirectionality of executive functioning (EF) and social competence supports a comprehensive evaluation of EF within intervention outcomes. Existing data from a suite of four informant and performance measures frequented within EF literature were evaluated as a case example of the contribution of EF in relation to the impact of the Social Competence Intervention for Adolescents (SCI-A) curriculum on social competence. Analyses explored a more "child-world" approach to EF assessment within a context of general social competence gains. Key findings highlight students' improvements in broad, informant-based measures of executive function and in performance-based tasks designed to assess specific EF processes. Furthermore, these measures provide unique sources of information. Implications for the use of multisource executive function assessments within social competence interventions are discussed.